Neutrino Physics with the Precision IceCube Next Generation Upgrade (PINGU) - Palczewski, Tomasz; IceCube/PINGU Collaboration (Deutsches Elektronen-Synchrotron, DESY, 2014)
The IceCube Neutrino Observatory at the geographic South Pole is the largest neutrino telescope on Earth. IceCube and its low energy extension, DeepCore, were fully assembled at the end of 2010. DeepCore lowered the IceCube neutrino energy threshold to about 10 GeV, allowing access to a rich variety of atmospheric neutrino oscillation physics, and further improving sensitivity to indirect searches for WIMP dark matter and other phenomena.The recent measurements of a relatively large $θ_{13}$ mixing angle and the first observations of atmospheric neutrino oscillations in the tens of GeV region in DeepCore open the possibility to determine the Neutrino Mass Hierarchy (NMH) in the proposed new in-fill array called Precision IceCube Next Generation Upgrade (PINGU).PINGU would lower the neutrino energy threshold and significantly increase the sensitivity to the NMH. For every year of the PINGU detector operation, on the order of one hundred thousand atmospheric neutrinos will be collected. These high statistics will allow PINGU to distinguish between the normal and inverted NMH at 3$σ$ significance with an estimated 3.5 years of data.